2009
DOI: 10.1186/1471-2105-10-294
|View full text |Cite
|
Sign up to set email alerts
|

Detecting purely epistatic multi-locus interactions by an omnibus permutation test on ensembles of two-locus analyses

Abstract: Background: Purely epistatic multi-locus interactions cannot generally be detected via singlelocus analysis in case-control studies of complex diseases. Recently, many two-locus and multilocus analysis techniques have been shown to be promising for the epistasis detection. However, exhaustive multi-locus analysis requires prohibitively large computational efforts when problems involve large-scale or genome-wide data. Furthermore, there is no explicit proof that a combination of multiple two-locus analyses can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 78 publications
2
36
0
Order By: Relevance
“…A second area where we can expect continued development is the exploration of additional analytic approaches. Novel methods continue to emerge (Greene et al , 2010;Steffens et al , 2010;Wongseree et al , 2009). Finally, as gene sequencing continues to become cost effective, for gene-region, whole exome, and eventually whole genome sequencing, methods for looking for epistasis in these data will become critical.…”
Section: Future Workmentioning
confidence: 99%
“…A second area where we can expect continued development is the exploration of additional analytic approaches. Novel methods continue to emerge (Greene et al , 2010;Steffens et al , 2010;Wongseree et al , 2009). Finally, as gene sequencing continues to become cost effective, for gene-region, whole exome, and eventually whole genome sequencing, methods for looking for epistasis in these data will become critical.…”
Section: Future Workmentioning
confidence: 99%
“…Thameem et al (2002) concluded that polymorphism of this gene did not contribute significantly to T2D etiology in Pima Indians (Thameem et al, 2002). On the other hand, an evidence of association between two intronic SNPs of the LMX1A and T2D in the British population has been reported by Wongseree et al (2009).…”
Section: Discussionmentioning
confidence: 98%
“…Mutations in PARK2 have been associated with juvenile autosomal recessive Parkinsonism [13], leprosy [14], diabetes mellitus type 2 [15], Alzheimer’s dementia [16], multiple sclerosis [17], Attention Deficit Hyperactivity Disorder (ADHD) [18], autism [19], typhoid and paratyphoid fever [20, 21], and more recently to cancer [22]. Among the cancers already presenting PARK2 alterations are: ovarian, breast, kidney, lung, liver, colorectal, melanoma, acute lymphoblastic leukemia, Burkitt’s lymphoma, and B-cell non-Hodgkin’s lymphoma [23].…”
Section: Introductionmentioning
confidence: 99%